Pengaruh Komposisi Dedak Dan Ukuran Baglog Terhadap Produksi Jamur Tiram Putih (Pleurotus ostreatus) - Sitti Nurlina; Tutik Nugrahini; Hamidah Hamidah (Universitas Widya Gama Mahakam, 2019)
The study was conducted to determine the effect of bran composition and baglog size on the production of white oyster mushrooms (Pleurotus ostreatus). The study was arranged in a Randomized Block Design (RBD) consisting of 2 factors with 5 replications. The first factor is the composition of bran consisting of four levels, namely: 10%, 15%, 20% and 25%. The second factor is the size of baglog which consists of 4 levels, namely: 17 cm, 18 cm, 19 cm and 20 cm. The results showed that the composition of bran had a very significant effect on the age of the first harvest, average mushroom weight, average fresh weight per baglog and biological efficiency ratio. Baglog size has a significant effect on the age of the first harvest, average mushroom weight, average fresh weight per baglog and biological efficiency ratio. The best effect on the production of oyster mushrooms is produced by the composition of bran 20% (d3) and baglog size of 19 cm (b3). The interaction of bran composition and baglog size significantly affected the age of the first harvest and had a very significant effect on the average weight of mushrooms, but did not significantly affect the fresh weight of mushrooms per baglog and the ratio of biological efficiency. The best interaction with the production of white oyster mushrooms is a combination of 20% bran composition and 19 cm baglog size.